Factors of social infrastructure development in rural areas. Issue 1 (September 2021) - Akifieva, L; Nechaeva, M; Polyakov, M; Sidorova, N; Gruzdev, G
Abstract: The article considers the influence of social and economic factors on the level of development of rural areas. These factors can help to assess patterns and dependencies to obtain directions that serve as the basis for further strategic planning in relation to the sustainable development of social infrastructure of rural areas. Methods of factor analysis, monographic method, observation, generalizations were used as the main methods of research. The information base is statistics on Nizhny Novgorod region, regulatory legal acts. The results of analytical assessment of enlarged indicators of rural development in Nizhny Novgorod region are given. The role of national strategy and targeted programs in financing rural development is noted. The article presents the results of parameters' research of social and economic development, according to residents of municipal districts on the example of Nizhny Novgorod region. The main purpose of the monitoring is to analyze conditions and factors of development requiring the attention of authorities on the first place. The author's research methodology was based on statistical and economic tools and methods of data analysis. As the result of research, problems of development of municipal districts were identified; key development factors were revealed as the main directions for management decisions.